Mergers and Investment Incentives - John, Teresa A. (Journal of Financial and Quantitative Analysis, 1986)
This paper explores the effects of mergers on the investment incentives of the levered firm and on levered firm value. Under a fairly broad set of assumptions, it is shown that most firm combinations “improve” investment incentives, bringing about a reduction in the agency costs of underinvestment associated with risky debt. The effect of the merger on debt and equity claim values is also explored. If not properly anticipated, the merger may create a wealth transfer from equity holders to bondholders. Such a wealth transfer includes, but is not limited to, the “coinsurance effect.”